2015
DOI: 10.1002/asi.23445
|View full text |Cite
|
Sign up to set email alerts
|

Bibliogifts in LibGen? A study of a text‐sharing platform driven by biblioleaks and crowdsourcing

Abstract: Research papers disseminate the knowledge produced by the scientific community. Access to this literature is crucial for researchers and the general public. Apparently 'bibliogifts' are available online for free from text-sharing platforms. However, little is known about such platforms. What is the size of the underlying digital libraries? What are the topics covered? Where do these documents originally come from? This paper reports a study of the Library Genesis platform (LibGen). The 25 million documents (42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 34 publications
0
36
0
4
Order By: Relevance
“…Cabanac [1] reveals that 36% of all digital object identifier (DOI) articles are available for free at Library Genesis platform (LibGen). For the three major publishers (Elsevier, Springer and Wiley) the percentage is even higher (68%).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Cabanac [1] reveals that 36% of all digital object identifier (DOI) articles are available for free at Library Genesis platform (LibGen). For the three major publishers (Elsevier, Springer and Wiley) the percentage is even higher (68%).…”
Section: Related Workmentioning
confidence: 99%
“…Users crowdsource articles to LibGen directly or indirectly through services such as Reddit Scholar and SciHub. Cabanac [1] also claims that people crowdsource articles through various other channels such as Reddit, Sci-Hub, #icanhazpdf hashtag on Twitter, personal websites and text-sharing platforms.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Another response to these shifts in the academic publishing world is what has been termed Guerilla Open Access 1 , Bibliogifts 10 or Black Open Access 11 . Or in short, the usage of semi-legal or outright illegal ways of accessing scholarly publications, like peer2peer file sharing, for example the use of #icanhazpdf on Twitter 10 , or centralized web services like Sci-Hub / LibGen 12 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most extensive studies to date was conducted by Cabanac, who examined full-text content available on the Library Genesis (LibGen) platform. LibGen hosted over 25 million documents at the time of the study; 36% of all articles assigned a digital object identifier (DOI) were found to be available on the platform, with 71% of the content originating from massive paper uploads and 29% originating from crowd-sourced sites [5].…”
Section: Introductionmentioning
confidence: 99%